Training for university teaching: The tendency of the Post-Graduate Nursing Programs in Brazil - Katheri Maris Zamprogna; Vânia Marli Schubert Backes; Jouhanna Do Carmo Menegaz; Fernanda Moreira Ribeiro Fraga; Francisco Reis Tristão; Gilberto Tadeu Reis da Silva (Universidade Federal de Santa Maria, 2020)
Objective: To characterize the subjects of the stricto sensu Post-Graduate Nursing Programs curricula focused on didactic-pedagogical training. Method: An exploratory-descriptive research, of documentary analysis in the curricula of stricto sensu Post-Graduate Nursing Programs and in the teaching plans of the didactic-pedagogical subjects. The disciplinary teaching plans of the 27 stricto sensu Post-Graduate Nursing Programs in Brazil were analyzed, with 53 plans submitted to descriptive statistical analysis. Data collection took place from March to June 2016. Results: Characteristics were presented regarding the curriculum of the programs, focusing on the themes, contents, and teaching strategies of the didactic-pedagogical subjects. Conclusion: There are differences among the curricula regarding the fundamental didactic-pedagogical subjects and the contents and teaching strategies. There was a need to develop the valorization of the teaching dimension in the stricto sensu Nursing Programs.